The Role Of Instagram In Constructing The Ideal Mother - Shulbi Putri; Neni Yulianita; Ferry Darmawan (Mediator: Jurnal Komunikasi, 2025)
Motherhood has increasingly become a topic shaped and negotiated in digital spaces, especially on social media. This study examines how Instagram shapes the construction of the "ideal mother" through the experiences of young mothers who actively use the platform. Using a qualitative approach, this research explores the negotiation process between societal expectations and personal realities in mothering. In-depth interviews with selected informants reveal that while Instagram serves as a practical and inspirational source of parenting knowledge, it also imposes emotional pressure due to the prevailing social norms of ideal motherhood. The findings suggest that young mothers actively filter and adapt information according to their unique family contexts, demonstrating agency in their engagement with digital motherhood narratives. Furthermore, this study highlights Instagram's dual role in shaping young mothers' behavior. While it offers a supportive community and valuable parenting insights, it also fosters unrealistic expectations that can lead to stress and anxiety. Understanding this dynamic is essential for future discussions on media literacy and the psychological effects of social media on parenting identities. This study contributes to the broader discourse on digital motherhood and offers insights into how social media platforms can be leveraged to provide more balanced and diverse representations of motherhood.